2007
DOI: 10.1371/journal.pone.0000799
|View full text |Cite
|
Sign up to set email alerts
|

Phage-Antibiotic Synergy (PAS): β-Lactam and Quinolone Antibiotics Stimulate Virulent Phage Growth

Abstract: Although the multiplication of bacteriophages (phages) has a substantial impact on the biosphere, comparatively little is known about how the external environment affects phage production. Here we report that sub-lethal concentrations of certain antibiotics can substantially stimulate the host bacterial cell's production of some virulent phage. For example, a low dosage of cefotaxime, a cephalosporin, increased an uropathogenic Escherichia coli strain's production of the phage ΦMFP by more than 7-fold. We name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
358
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 350 publications
(389 citation statements)
references
References 17 publications
26
358
2
3
Order By: Relevance
“…This is in contrast with previous studies reporting beneficial effects of phage–antibiotic combinations on Escherichia coli biofilms (Ryan, Alkawareek, Donnelly, & Gilmore, 2012) and planktonic P. aeruginosa cultures (Torres‐Barceló et al., 2016). However, phage–antibiotic effects are not always observed (Verma et al., 2009), which could be due to the specific phage species and class of antibiotic as PAS often requires mechanistic compatibility between the two (Chan et al., 2016; Comeau et al., 2007; Kamal & Dennis, 2015). For example, it has recently been reported that associations between phage and gentamycin resistance are predominantly positive, while associations between phage and ciprofloxacin resistance are mainly negative with natural and clinical E. coli isolates (Allen, Pfrunder‐Cardozo, Meinel, Egli, & Hall, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in contrast with previous studies reporting beneficial effects of phage–antibiotic combinations on Escherichia coli biofilms (Ryan, Alkawareek, Donnelly, & Gilmore, 2012) and planktonic P. aeruginosa cultures (Torres‐Barceló et al., 2016). However, phage–antibiotic effects are not always observed (Verma et al., 2009), which could be due to the specific phage species and class of antibiotic as PAS often requires mechanistic compatibility between the two (Chan et al., 2016; Comeau et al., 2007; Kamal & Dennis, 2015). For example, it has recently been reported that associations between phage and gentamycin resistance are predominantly positive, while associations between phage and ciprofloxacin resistance are mainly negative with natural and clinical E. coli isolates (Allen, Pfrunder‐Cardozo, Meinel, Egli, & Hall, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Positive correlation between phage selection and antibiotic resistance is in contrast with previous studies showing an opposite effect where phage treatment reduced the emergence of antibiotic resistance (Jalasvuori, Friman, Nieminen, Bamford, & Buckling, 2011; Zhang & Buckling, 2012). One explanation for this discrepancy is that phage–antibiotic synergies could be very specific to the given phage species and type of antibiotics, whereas antibiotic selection‐mediated susceptibility to phages could have been driven by some degree of collateral sensitivity (Chan et al., 2016; Comeau et al., 2007; Kamal & Dennis, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La phagothé-rapie a cependant continué d'exister jusqu'à ce jour en ex-Union soviétique, en particulier en République de Géor-gie, grâce à l'Institut George Eliava cofondé par d'Hérelle et Eliava dans les années 1920 [7]. [9]. L'addition à des cultures bactériennes de faibles doses d'antibiotiques qui bloquent la division cellulaire et induisent la formation de filaments, comme le font les céphalosporines, augmente de façon significative la production de phages.…”
Section: L'activité Antibactérienne Des Phages : Un Regain D'intérêtunclassified
“…croissant de travaux souligne une synergie d'action entre phage et antibiotique, notamment en présence de concentration sub-inhibitrice d'antibiotique, comme rencontré dans le cas d'infections avec des souches de sensibilité intermédiaire aux antibiotiques [21].…”
Section: Des Virus Issus De L'environnement Bientôt Transformables àunclassified